Proposed new interior design of House Of Healin Spa for Majoriz Enterprise at No 11F, 11G, 13, 15, 17 &19 Lot 1238 Lebuh Buckingham, 10200, Georgetown, Penang / Nor Akma Muhamad - Muhamad, Nor Akma (Faculty of Architecture, Planning and Surveying, 2010)
All final student of Diploma in Interior Architecture should be completed every stage of their final design. This is to analysis toward student’s knowledges about interior design from basic to the final presentation in board.Propose new interior design of House of Healin Spa for Majoriz Enterprise at Georgetown, Penang has being chosen for this final project. This is because, the client would like to open up new branch at Penang and House of Healin is one of the famous brand in Malaysia. Besides, it also to introduce about House of Healin product in the market. The concept and image that used for this spa must be reflect with client’s needed and the theme of the HQ House of Healin. Besides, through interviews, observation, media, internet and case study some of information can be use to finish this project.